PENGARUH RISIKO USAHA DAN GOOD CORPORATE GOVERNANCE TERHADAP SKOR KESEHATAN BANK PADA BANK UMUM SWASTA NASIONAL DEVISA - Dhita Dhora Damayanti; Herizon Chaniago (STIE Perbanas Surabaya, 2014)
The purpose of research is to find out whether NPL, CKPN Credit, IRR, PDN, LDR, IPR,BOPO, FBIR, and GCG have a significant influence either simultaneously or partially towardsBanks Determining Health Score. It used a population at the National Private CommercialBank Foreign Exchange. The sample was selected based on sampling techniquesusing purposive sampling technique and used documentation data. Based on the calculationsand the results obtained testing the hypothesis that simultaneous variables NPL, CKPNCredit, IRR, PDN, LDR, IPR, BOPO, FBIR, and GCG have a significant influence on DeterminingHealth Score. It means that credit risk, market risk, liquidity risk, operational riskand GCG have significant influence to determining health score. While partially NPL, CKPNCredit, IRR, PDN, have no significant effect, IPR has no positive significant effect, LDR hasa positive effect significant, and BOPO has a negative significant effect. Among the sevenvariables, the most dominant is LDR, compared with the highest coefficient of determinationof the other independent variables.